2016
DOI: 10.3343/alm.2016.36.4.325
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Acinetobacter Species Using Matrix-Assisted Laser Desorption Ionization-Time of Flight Mass Spectrometry

Abstract: BackgroundAcinetobacter baumannii has a greater clinical impact and exhibits higher antimicrobial resistance rates than the non-baumannii Acinetobacter species. Therefore, the correct identification of Acinetobacter species is clinically important. Matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) mass spectrometry (MS) has recently become the method of choice for identifying bacterial species. The purpose of this study was to evaluate the ability of MALDI-TOF MS (Bruker Daltonics GmbH, Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…baumannii isolates at the species level (57, 33, 34), difficulties seem to arise with MS when it is applied for strain-level identification of A. baumannii isolates (4, 811).…”
Section: Discussionmentioning
confidence: 99%
“…baumannii isolates at the species level (57, 33, 34), difficulties seem to arise with MS when it is applied for strain-level identification of A. baumannii isolates (4, 811).…”
Section: Discussionmentioning
confidence: 99%
“…Similarity analyses of the 16S rRNA sequences were conducted using BLASTn (https://blast.ncbi.nlm.nih.gov/Blast.cgi). A phylogenetic tree was produced by using the neighbor-joining algorithms with the Molecular Evolutionary Genetics Analysis 7 (MEGA 7) software based on BLAST results of the 16S rRNA sequence [15]. Antimicrobial susceptibility tests were performed to determine the MICs for carbapenems based on the breakpoints de ned by the Clinical and Laboratory Standards Institute [4].…”
Section: Isolation and Identi Cation Of The Carbapenem-resistant Stramentioning
confidence: 99%
“…This is mainly due to their close phenotypic and genetic relatedness [6]. Non baumannii species differ from A. baumannii in terms of antibiotic susceptibility [29]. Lee et al found that non baumannii strains were more resistant to colistin than their counterparts; for instance, Acinetobacter genomospecies 14TU are shown to have natural resistance to colistin [29].…”
Section: Acinetobacter Baumannii In Lebanon: a Real Threat Or An Overmentioning
confidence: 99%
“…Non baumannii species differ from A. baumannii in terms of antibiotic susceptibility [29]. Lee et al found that non baumannii strains were more resistant to colistin than their counterparts; for instance, Acinetobacter genomospecies 14TU are shown to have natural resistance to colistin [29]. One study conducted in Japan, used MALDI-TOF for the identification of Acinetobacter spp isolated from blood cultures.…”
Section: Acinetobacter Baumannii In Lebanon: a Real Threat Or An Overmentioning
confidence: 99%
See 1 more Smart Citation